Usability, inclusivity, and content evaluation of COVID-19 contact tracing apps in the United States. (22nd June 2021) - Blacklow, Serena O; Lisker, Sarah; Ng, Madelena Y; Sarkar, Urmimala; Lyles, Courtney
Abstract: We evaluated the usability of mobile COVID-19 contact tracing apps, especially for individuals with barriers to communication and limited digital literacy skills. We searched the Apple App Store, Google Play, peer-reviewed literature, and lay press to find contact tracing apps in the United States. We evaluated apps with a framework focused on user characteristics and user interface. Of the final 26 apps, 77% were on both iPhone and Android. 69% exceeded 9th grade readability, and 65% were available only in English. Only 12% had inclusive illustrations (different genders, skin tones, physical abilities). 92% alerted users of an exposure, 42% linked to a testing site, and 62% linked to a public health website within 3 clicks. Most apps alert users of COVID-19 exposure but require high English reading levels and are not fully inclusive of the U.S. population, which may limit their reach as public health tools.